2019
DOI: 10.1136/bjsports-2018-100035
|View full text |Cite
|
Sign up to set email alerts
|

Exercise alone and exercise combined with education both prevent episodes of low back pain and related absenteeism: systematic review and network meta-analysis of randomised controlled trials (RCTs) aimed at preventing back pain

Abstract: ObjectivesWe aimed to investigate which prevention strategies for low back pain (LBP) are most effective.DesignWe completed a Bayesian network meta-analysis to summarise the comparative effectiveness of LBP prevention strategies. The primary outcomes were an episode of LBP and LBP-associated work absenteeism represented as ORs with associated 95% credibility intervals (CrIs). We ranked all prevention strategies with surface under the cumulative ranking curve (SUCRA) analysis.Data sourcesPubMed, EMBASE and CENT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 74 publications
4
38
1
8
Order By: Relevance
“…Low back pain is a multifactorial disease that involve physical and psychological sphere. Even if exercise is one of the most efficient strategies for the management and prevention of LBP (19), our results showed contrast results. The analysis of participants showed a reduction of pain in 5 out 18 participants, an unchanged pain in 6 out 18, while 7 participants worsened their LBP.…”
Section: Discussioncontrasting
confidence: 79%
“…Low back pain is a multifactorial disease that involve physical and psychological sphere. Even if exercise is one of the most efficient strategies for the management and prevention of LBP (19), our results showed contrast results. The analysis of participants showed a reduction of pain in 5 out 18 participants, an unchanged pain in 6 out 18, while 7 participants worsened their LBP.…”
Section: Discussioncontrasting
confidence: 79%
“…Low back pain (LBP) has a high prevalence during life, and the costs for society in Europe are extremely high [1][2][3]. LBP is caused by the interaction of physical disfunction, anatomical variables, and psychosocial comorbidities, e.g., sedentary life or depression [4,5]. In up to 90% of all patients, low back pain is considered non-specific, since no specific cause can be detected [6].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced pain may represent an additional mechanism through which regular exercise eases sleep issues, such as insomnia. For instance, a recent meta-analysis involving 40 randomized clinical trials has shown that exercise can prevent low back pain [ 103 ], which is the most common type of chronic pain and is often associated with low sleep quality [ 104 ]. Finally, type, duration, and timing of exercise, a person's condition (disease, trained, untrained, age, gender), and genetics may alter the myokine response to exercise and are, therefore, important variables to consider.…”
Section: Important Considerationsmentioning
confidence: 99%